Finishing Beef - Jones, Rodney D. (My University, 2007)
This publication helps a producer that buys feeder calves and then finishes them, and uses projected input and output prices for illustrative purposes to find the break-even price.
MF592_2007_10
Keywords: MF592; Economics; Livestock; MF